Memaknai Persatuan dalam Kehidupan Multikultural sebagai Penangkal Radikalisme - Darul Lailatul Qomariyah (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
Indonesia as a country that stands on cultural diversity requires the importance of multiculturalism in nation building. With this multiculturalism, the principle of